Our gloomy future and glorious past: societal discontent, national nostalgia and support for populist radical-right parties in the Netherlands - Smeekes, Anouk; Lubbers, Marcel (Frontiers in Political Science, 2024)
Political campaign slogans, such as “Make America Great Again” or “The Netherlands Ours Again”, indicate that right-wing populists in Western countries use nostalgia to depict the national past as glorious. At the same time, populist radical-right parties (PRRP) portray this glorious past as being in stark contrast with the gloomy present of their country, which is portrayed as being in a state of decline. This suggests that PRRP in Western societies draw on both societal discontent (i.e., the belief that society is in decline and poorly functioning) and national nostalgia (i.e., a longing for the good old days of the country) to mobilize their voters. Although there is a burgeoning literature on reasons for PRRP electoral support, fewer studies have focused on its emotional or affective underpinnings. While scholars have proposed that both societal discontent and national nostalgia are an integral piece of a new master-frame employed by PRRP in Western countries to increase their electoral appeal, these elements have hardly been empirically studied in reference to voters. Relying on an integration of research in political science and social psychology, we hypothesized that both societal discontent and national nostalgia go together with a greater sympathy, and likelihood of voting, for PRRP. In addition, we predicted that national nostalgia is an explanatory mechanism that links societal discontent to more support for PRRP. These hypotheses were tested in the context of the Netherlands, among a representative sample of native Dutch voters, using the Dutch Parliamentary Elections Survey of 2021. Results demonstrated that while both societal discontent and national nostalgia were relevant predictors of PRRP support, there was no strong evidence for national nostalgia as an explanatory mechanism of the link between societal discontent and PRRP support.